Financial Risk Analytics for Informed Sovereign Disaster Risk Financing Decision Making - World Bank (Washington, DC, 2015)
Evaluating the level of financial protection and associated costs of sovereign disaster risk financing and insurance (DRFI) decisions is challenging. DRFI strategies are often presented as a combination of financial instruments, such as domestic reserves, contingent credit and catastrophe risk transfer instruments. However, governments usually lack tools to help them evaluate and quantify the costs and benefits of such strategies and answer questions like: what should be the annual budget allocation for post-disaster response? What should be the size of domestic reserves? What should be the amount of contingent credit? Shall government purchase catastrophe risk transfer instruments? Financial risk analytics helps the decision makers evaluate the financial costs and benefits of sovereign DRFI strategies. Understanding the financial implications of alternative sovereign DRFI strategies requires detailed financial analysis. For example, understanding the tradeoff between the quality of financial coverage and its price requires some quantitative financial analysis. The results of financial analysis can also be used to document and justify the process of sovereign DRFI decision making.